(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2022)
The Covid-19 pandemic tragically emphasized severe failures of health systems. In particular, the saturation of hospital infrastructures and the lack of medical devices is crucial for respiratory ventilators. The medical and pharmaceutical sectors had to find urgently new ways to innovate efficiently in R&D, to produce devices, therapeutic trials, and vaccines, and make them available on a large scale. Our work will analyze that these innovations related to Covid-19 have been largely based on Open Innovation. For that purpose, exploratory case studies will be shown that exemplify the value of implementing Open Innovation in the pandemic context. These case studies concern the pharmaceutical firm Pfizer, the biotechnology company BioNTech, and the respiratory ventilator open development coalition OxyGEN (from design company Protofy. xyz to the hospitals’ network of Barcelona and manufacturer SEAT). Methodologically, these case studies build on a full referencing and systematic analysis of articles, scientific documents, and published reports related to the Open Innovation involvement of these organizations since the start of the pandemic. Based on the operative contributions from these revelatory case studies, we can show that Open Innovation is a highly efficient vector for extended partnerships for accelerated R&D and operational production contextually to pandemic emergencies.